Analysis of students' errors in solving quadratic equation word problems based on Watson's criteria - Azin Taufik; Anggar Titis Prayitno; Tika Nuanatul Mufida; Galuh Nuril Lathifah (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2024)
This research is motivated by the phenomenon of low student ability in solving word problems in mathematics, indicating significant challenges in understanding and applying mathematical concepts in real-life contexts. The aim of this study is to describe the errors made by students and the factors contributing to these errors in solving word problems based on Watson's criteria. This research employs a descriptive qualitative approach. The data collection methods used include tests and interviews. A total of 29 tenth-grade students from SMA Negeri Cigugur were given test problems, and subsequently, 16 students were selected as research subjects, representing each of Watson's error criteria. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the most common types of errors made by students include omitted data (OD), inappropriate procedures (IP), such as incorrect procedures, response level conflicts (RLC), and inappropriate data (ID). Some of the factors contributing to these errors include failure to draw conclusions from the obtained data, lack of understanding of quadratic equations, and insufficient student preparation in solving problems. On the other hand, less frequently occurring errors include above other (AO), omitted data (OD), undirected manipulation (UM), and skill hierarchy problems (SHP). The factors causing these less frequent errors are generally related to students' lack of attention to detail and accuracy in problem-solving. This research provides significant contributions as a foundation for teachers to design more effective teaching strategies, particularly in enhancing students' conceptual understanding and problem-solving skills.